NRF2: A crucial regulator for mitochondrial metabolic shift and prostate cancer progression - Buttari, Brigitta; Arese, Marzia; Oberley-Deegan, Rebecca E.; Saso, Luciano; Chatterjee, Arpita (Frontiers in Physiology, 2022)
Metabolic alterations are a common survival mechanism for prostate cancer progression and therapy resistance. Oxidative stress in the cellular and tumor microenvironment dictates metabolic switching in the cancer cells to adopt, prosper and escape therapeutic stress. Therefore, regulation of oxidative stress in tumor cells and in the tumor-microenvironment may enhance the action of conventional anticancer therapies. NRF2 is the master regulator for oxidative stress management. However, the overall oxidative stress varies with PCa clinical stage, metabolic state and therapy used for the cancer. In agreement, the blanket use of NRF2 inducers or inhibitors along with anticancer therapies cause adverse effects in some preclinical cancer models. In this review, we have summarized the levels of oxidative stress, metabolic preferences and NRF2 activity in the different stages of prostate cancer. We also propose a condition specific ways to use NRF2 inducers or inhibitors along with conventional prostate cancer therapies. The significance of this review is not only to provide a detailed understanding of the mechanism of action of NRF2 to regulate oxidative stress-mediated metabolic switching by prostate cancer cells to escape the radiation, chemo, or hormonal therapies, and to grow aggressively, but also to provide a potential therapeutic method to control aggressive prostate cancer growth by stage specific proper use of NRF2 regulators.